Wellbeing, social media addiction and coping strategies among Chilean adolescents during the pandemic - Varela, Jorge J.; Pérez, Janet Carola; Rodríguez-Rivas, Matías E.; Chuecas, María Josefina; Romo, Javiera (Frontiers in Psychiatry, 2023)
During the COVID-19 pandemic, adolescents had to deal with a range of mental health problems due to local and national quarantine policies. This situation has increased internet use among adolescents, in turn boosting social media addiction levels with adverse effects on life satisfaction. Previous studies have explored coping mechanisms to deal with this addiction problem, but did not consider the need to simultaneously cope with different dimensions within the pandemic context. Therefore, our study aimed to examine the moderating effect of various coping mechanisms on the relationship between social media addiction and adolescent life satisfaction. We used a sample of 1,320 students attending online secondary school classes. The mean age was 16.03 years old (SD = 1.27, range: 14 to 19) with 57% (n = 753) female participants. We found that the social media addiction risk was negatively associated with life satisfaction, adaptive strategies were positively correlated to life satisfaction, and maladaptive strategies were negatively correlated to it. Also, a moderation model was evaluated in which four stress management strategies, namely acceptance and perspective-taking, seeking socio-emotional support, active coping, and maladaptive strategies all conditioned the relationship between social media addiction risk and life satisfaction after controlling for demographic variables (age and sex) and the specific strategies of using comedy, religion and substance use. Results indicate additive and multiplicative effects of management strategies for stressful situations in the studied relationship. Seeking socio-emotional support and active coping were positively related to life satisfaction and maladaptive strategies were negatively associated with it. Multiplicative effects indicate that the relationship between the social media addiction risk and life satisfaction depends only on the acceptance and perspective-taking that adolescents report. When adolescents reported having low or average levels of acceptance and perspectivetaking, there was a negative correlation with general life satisfaction, a connection that grew markedly stronger. In contrast, no connection between social media addiction and life satisfaction was detected for adolescents who report higher levels of acceptance and perspective-taking. Abuse of social media and the use of maladaptive stress coping strategies were risk factors that decreased life satisfaction among adolescents during the COVID-19 pandemic period.